2021
DOI: 10.7150/ijms.55023
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of postoperative hypothermia and its risk factors in adults undergoing orthopedic surgery under brachial plexus block: A retrospective cohort study

Abstract: Postoperative hypothermia increases patient mortality and morbidity. However, the incidence of, and risk factors for, postoperative hypothermia in patients undergoing surgery under brachial plexus block (BPB) as the primary method of anesthesia remain unclear. This study aimed to determine the incidence of, and risk factors for, postoperative hypothermia in patients undergoing surgery under BPB. We retrospectively analyzed 660 patients aged ≥ 19 years who underwent orthopedic surgery under BPB in our hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 31 publications
(23 reference statements)
5
17
0
Order By: Relevance
“…In this study, a longer duration of surgery increased the risk for hypothermia. This observation was consistent with results from most studies on surgical populations [ 18 , 30 , 31 ]. Heat loss begins from surgical skin preparation [ 32 ], and continues in the first hour after induction of anesthesia, as the core temperature usually decreases by 1–1.5°C [ 33 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, a longer duration of surgery increased the risk for hypothermia. This observation was consistent with results from most studies on surgical populations [ 18 , 30 , 31 ]. Heat loss begins from surgical skin preparation [ 32 ], and continues in the first hour after induction of anesthesia, as the core temperature usually decreases by 1–1.5°C [ 33 ].…”
Section: Discussionsupporting
confidence: 92%
“…Although we observed that factors such as age and longer duration of surgery were associated with intraoperative hypothermia, it should be noted that fewer interventions can be implemented with these factors. Since higher baseline core temperature effectively protected patients against intraoperative hypothermia in our study, and the same effect was obtained in previous studies [ 13 , 31 ], measures can be taken to increase the patient’s baseline core body temperature to an appropriate range before anesthesia. Recently, active warming approaches, such as the use of forced air, have focused mostly on warming the skin surface [ 34 ].…”
Section: Discussionsupporting
confidence: 78%
“…The incidence of 60% of patients with temperatures below 36°C and 19% with temperatures below 35°C is compatible with those reported in several other comparable studies [ 4 , 14 , 15 ]. Kongsayreepong et al [ 16 ] found that 57% of the 194 surgical patients in the ICU had a tympanic temperature below 36°C, and 28% had a temperature below 35°C.…”
Section: Discussionsupporting
confidence: 91%
“…We found that older patients, patients with more comorbidities, and patients who had undergone longer surgeries were more likely to have hypothermia in the ICU. These associations have been reported in the literature [ 4 , 14 , 19 ], indicating that these patients have unfavorable outcomes [ 20 , 21 ].…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation